Simulation of the process of water purification in multilayered micro porous media (MCIT: Proceedings of International scientific and practical conference, 2019)
The mathematical model of the process of adsorption purification of water from impurities in multilayer microporous filters is formulated. An algorithm for numerically-asymptotic approximation of solution of the corresponding nonlinear singularly perturbed boundary value problem is developed. The developed model allows to investigate the distribution of concentration of pollutant inside the filer.
Keywords: mathematical model, process of water purification, micro porous media